2016
DOI: 10.1016/j.psyneuen.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progesterone stimulated allopregnanolone on craving and stress response in cocaine dependent men and women

Abstract: Objectives Fluctuations in progesterone levels during the menstrual cycle have been shown to affect physiological and subjective effects of cocaine. Furthermore, our laboratory has demonstrated that following drug-cue exposure, cocaine dependent women with high levels of circulating progesterone display lower diastolic and systolic blood pressure responses and report lower levels of anxiety and drug craving compared to cocaine dependent women with low levels of progesterone. In the current study we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 68 publications
1
56
1
Order By: Relevance
“…A recent study in humans by Milivojevic et al (2016) showed similar results, as allopregnanalone, a metabolite of progesterone, improved Stroop performance, a measure related to impulsive action. However, the beneficial effects of PRO may be specific to this particular subtype of impulsivity, as recent evidence from our laboratory showed no effect of PRO on impulsive choice for sucrose pellets in females and males, measured by a delay discounting task (Smethells et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A recent study in humans by Milivojevic et al (2016) showed similar results, as allopregnanalone, a metabolite of progesterone, improved Stroop performance, a measure related to impulsive action. However, the beneficial effects of PRO may be specific to this particular subtype of impulsivity, as recent evidence from our laboratory showed no effect of PRO on impulsive choice for sucrose pellets in females and males, measured by a delay discounting task (Smethells et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Milivojevic et al (2016) showed no sex differences in a measure of inhibitory control in humans. Anker et al (2008) also reported similar baseline rates of responding across males and females in impulsive action for sucrose pellets using a modified (i.e., extinction) No-Go component.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a follow-up study, we measured basal levels of the neurosteroid ALLO while on 5 days of progesterone versus placebo to assess if progesterone effects in this study were due to increased levels of ALLO. Indeed, we found that the high ALLO group (treated with progesterone) versus the low ALLO group showed reduced overall drug and alcohol craving, improved Stroop performance, and both reductions in basal cortisol levels as well as increased cortisol in response to stress (Milivojevic et al, 2016). While there are no direct data on neurosteroid treatment in alcohol dependent individuals, these data support our notion that compounds and approaches that normalize HPA axis function need to be explored to fully test whether addressing this stress-related pathophysiology in alcohol use disorders with specific targeted treatments may be helpful in improving alcoholism relapse and recovery outcomes.…”
Section: Alcohol-related Stress Adaptations: Implications For Alcomentioning
confidence: 88%
“…For example, COC’s rewarding stimulant effects seen in the follicular phase could have been counteracted by PRO’s anxiolytic effects (Nyberg et al 2006; Schneider and Popik 2007) to reduce intake during the follicular phase. In contrast, higher PCP intake in the luteal phase may have been due to alleviation of dysphoric effects of PCP by putative anxiolytic effects of PRO (Llaneza and Frye 2009; Schneider and Popik 2007) or its metabolite, allopregnanolone (ALLO) (Milivojevic et al 2016). Elevated PRO did not decrease cocaine self-administration in previous studies (Mello et al 2007; Cooper et al 2013), but exogenously-administered PRO decreased cocaine self-administration in female rhesus monkeys (Mello et al 2011).…”
Section: Discussionmentioning
confidence: 99%